2015
DOI: 10.1099/jmm.0.000099
|View full text |Cite
|
Sign up to set email alerts
|

Infections and cardiovascular disease: is Bartonella henselae contributing to this matter?

Abstract: Infections and cardiovascular disease: is Bartonella henselae contributing to this matter? Cardiovascular disease is still the major cause of death worldwide despite the remarkable progress in its prevention and treatment. Endothelial progenitor cells (EPCs) have recently emerged as key players of vascular repair and regenerative medicine applied to cardiovascular disease. A large amount of effort has been put into discovering the factors that could aid or impair the number and function of EPCs, and also into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 121 publications
0
6
0
Order By: Relevance
“…It has been proposed that B. henselae infection of endothelial progenitor cells could reduce both the number of these cells and their functionality (216). In so doing, the natural repair role for endothelial progenitor cells would be diminished, thereby indirectly contributing to the growth of atherosclerotic plaque (217). Further study is needed to support the role of the interaction of Bartonella with both endothelial progenitor cells and endothelial cells.…”
Section: Bartonella and Disease Disease Syndromes Associated With Barmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been proposed that B. henselae infection of endothelial progenitor cells could reduce both the number of these cells and their functionality (216). In so doing, the natural repair role for endothelial progenitor cells would be diminished, thereby indirectly contributing to the growth of atherosclerotic plaque (217). Further study is needed to support the role of the interaction of Bartonella with both endothelial progenitor cells and endothelial cells.…”
Section: Bartonella and Disease Disease Syndromes Associated With Barmentioning
confidence: 99%
“…Bartonella species share the ability to infect erythrocytes in their natural hosts, and it has been speculated that a primary niche exists to allow persistence of these bacteria in the host and to seed the bloodstream for subsequent transmission by the arthropod vector. The preponderance of evidence supports the role of the endothelium in serving as this primary niche (296), but it has also been suggested that endothelial progenitor cells may also function as a niche reservoir (215)(216)(217)308). Intracellular survival in endothelial cells would afford an opportunity for immune evasion and may explain the stealthy nature of these pathogens (223).…”
Section: Growth In Biofilmsmentioning
confidence: 99%
“…Myocarditis and pericarditis have been described [ 15 ]. Moreover, as B. henselae has been found able to infect endothelial cells and reduce their number and functionality, it has been supposed that this pathogen could play a role in the determination of acute and long-term vascular alterations [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The real importance of the prescribed antibiotic treatment for the resolution of this case could be debated, as the efficacy of antibiotics in atypical CSD cases is not precisely defined and official recommendations are lacking. Suggestions for antibiotic treatment are usually based only on personal experience and expert opinion [ 16 ]. However, the rapid improvement of all clinical manifestations of the disease, including the most severe ones, such as hepatic and splenic micro-abscesses, seems to indicate a possible direct effect of the antibiotic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…A murine model of chronic infection in immunocompromised SCID/Beige mice showed the ability of Bartonella to recapitulate human pathologies; indeed, in this model, bacteria grow in extracellular aggregates, embedded within collagen matrix similar to the observations in BA, BP, and catch-scratch disease (Chiaraviglio et al, 2010). In addition, B. henselae can infect and damage endothelial progenitors cells (EPCs) reducing the endothelium regenerating potential (Salvatore et al, 2008, 2015; Costa et al, 2010). …”
Section: Introductionmentioning
confidence: 99%